Grandparents Raising Grandchildren: Building Relationships - Part 2 - Millie Ferrer; Angela Falcone (EDIS)
This document is FCS 2191-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2002.  Its goal is to provide grandparents with knowledge and skills to develop positive family relationships.